'A Great and Holy War': Religious Routes to Women's Suffrage, 1909–1914*. (26th October 2019) - Saunders, Robert
Abstract: Looking back on the Edwardian suffrage campaign, the militant suffragette Annie Kenney thought it 'more like a religious revival than a political movement'. Its language and iconography were steeped in Christian imagery, yet the religious arguments for enfranchisement have rarely received close attention. This article shows how campaigners grappled with patriarchal readings of Genesis, St Paul and the traditions of the Church to construct a Christian case for equality. It focuses, in particular, on the Church League for Women's Suffrage, an Anglican organisation boasting nearly 6, 000 members by 1914. Inspired by the incarnational theology of Charles Gore, the League recruited over 500 clergy and eight bishops, convinced that enfranchisement was not merely compatible with, but actively demanded by, the teaching of Christ. Activists preached sermons, wrote pamphlets and debated theology in the religious press, establishing a powerful theological case for reform. Using the League as a case-study, the article explores the wider relationship between gender ideology and religious thought, at a time when Christianity was the central referent of British culture. Interrogating the religious roots of 'militancy', it shows how the conception of suffragism as a spiritual struggle collapsed any easy distinction between 'religion' and 'politics', establishing prayer, worship and Biblical exegesis as weapons of political warfare. The churches, it is concluded, did not simply respond to changing ideas about sex and gender; they were themselves sites of new thinking about the roles of men and women, forming one of the many tributaries that fed the flood-tide of feminist thought.